2018
DOI: 10.1016/j.amjcard.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Predictors of Outcomes in Patients With Pulmonary Hypertension

Abstract: In pulmonary hypertension (PH), measurement of various echocardiographic parameters that assess right heart function is recommended by current clinical guidelines. Limited data exists on the combined value of clinical and echocardiographic parameters in precapillary PH in the modern era of therapy. We examined the association of clinical and echocardiographic parameters with surrogate outcomes (6-minute walk distance) and hard outcomes (hospitalization or death) in patients with precapillary PH. A cohort of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Our analysis of sonographic, sonoelastographic, and clinical cardiac variables demonstrated that only TAPSE was associated with survival in patients with PAH. This result aligns with those of other studies in the literature that have reported this parameter to be a prognostic factor in PAH [ 34 - 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis of sonographic, sonoelastographic, and clinical cardiac variables demonstrated that only TAPSE was associated with survival in patients with PAH. This result aligns with those of other studies in the literature that have reported this parameter to be a prognostic factor in PAH [ 34 - 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…RV strain predicted survival when adjusted for pulmonary pressure, PVR, and RAP. 97 Siddiqui et al 98 found that RV GLS was associated with hospitalization or death (n ¼ 98, HR: 1.54 per 1 SD (5.31), 95% CI: 2.12, p ¼ 0.008). In a meta-analysis of 11 studies to examine RV strain n ¼ 1169 PH patients, a 19% reduction in RVLS had a higher risk of combined endpoint HR 1.22, and a 22% reduction in RV GLS had a higher risk of all-cause mortality HR 2.96.…”
Section: Noninvasive Imaging Of the Rv Echocardiographymentioning
confidence: 99%
“…L. Zerweck 1,2 , U. Henkemeier 2,3,4 , P. H. Nguyen 1,2 , T. Rossmanith 2,3 , A. Pippow 1,2 , H. Burkhardt 2,3,4,5 , F. Behrens 2,3,4,5 , M. Köhm 2,3,5 . 1 Background: Psoriasis (Pso) is one of the most common chronic inflammatory skin diseases in Europe.…”
Section: Assessment Of Fluorescence-optical Imaging Technique Of Thementioning
confidence: 99%
“…Zhang 1 , N. Zhang 1 , Y. Zhu 2 , Q. Wang 2 , L. Zhou 2 . 1 Nanjing Medical University, Nanjing, China; 2 The First Affiliated Hospital of Nanjing Medical University, Nanjing, China Background: Pulmonary arterial hypertension (PAH) is a fatal complication of connective tissue diseases (CTDs). Chest CT has been increasingly used in the evaluation of patients with suspected PH noninvasively but there is a paucity of studies.…”
Section: Ab1139mentioning
confidence: 99%